Bend Distortion and Thermal Lensing Effect on Transverse Mode Instability - Dan Cheng; Qing Zhong; Yujun Feng; Kun Zhang; Zhaochen Cheng; Dayong Zhang; Hong Zhao (Photonics)
In this work, we conducted a numerical analysis to investigate the combined effect of thermal lensing and bending-induced mode distortion on transverse mode instability in conventional large-mode-area (LMA) step-index fibers. Utilizing the finite element method, conformal mapping, and thermal conduction equations, we simulated the mode profiles in LMA 20/400 and 25/400 fibers subjected to both bending and thermal lensing effects; the corresponding evolution of mode loss and effective area were explored as well. Additionally, by introducing the derived mode profiles to the TMI coefficient calculations, we analyzed the influence of bending and thermal lensing (TL) on TMI; the simulation results indicate that the mode distortion caused by bending and the TL effect, under the bending conditions commonly encountered in practice, do not have pronounced impacts on TMI coefficient and TMI threshold.